2020
DOI: 10.12968/jowc.2020.29.10.572
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics of human juvenile, adult and murine fibroblasts: a comparison of polymer wound dressings

Abstract: Objective: Fibroblasts are important for the successful healing of deep wounds. However, the influence exerted by Cuticell, a natural polymer on fibroblasts and by the synthetic polymer, Suprathel, made of poly-L-lactic acid, is not sufficiently characterised. This study compared the survival and growth characteristics of human juvenile and adult dermal fibroblasts as well as murine fibroblast cell line L929, on a natural polymer with those of a synthetic polymer using different culture models. Method: Murine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Supporting these findings, animal weight development and behavior remained unaffected throughout the entire study. The previous in vitro studies indicated that the functionalization with gas-phase fluorination and a cross-linked collagen foam supported cell spreading and adherence on the scaffold (Gögele et al 2021(Gögele et al , 2020b. This preceding observation could be substantiated and expanded in the here given experiments.…”
Section: Discussionsupporting
confidence: 76%
“…Supporting these findings, animal weight development and behavior remained unaffected throughout the entire study. The previous in vitro studies indicated that the functionalization with gas-phase fluorination and a cross-linked collagen foam supported cell spreading and adherence on the scaffold (Gögele et al 2021(Gögele et al , 2020b. This preceding observation could be substantiated and expanded in the here given experiments.…”
Section: Discussionsupporting
confidence: 76%
“…In the present investigation, GFs were used to investigate the biomaterials for implant‐supported prostheses, as GFs are considered the key soft tissue cells for achieving stable STI (Rompen et al 2006) 25 . In order to obtain representative results despite the donor variation typical for primary cells, 26 cells from 5 donors were used. The performed cell culture experiments demonstrated a differential GF response for all donors depending on the manufacturing process of the specimens, which was either 3D printing or subtractive manufacturing.…”
Section: Discussionmentioning
confidence: 99%